(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: Nutritional outcomes in children under five are influenced by household environmental and water sanitation practices. This study aimed to assess the relationship between these practices and nutritional outcomes (HAZ, WAZ, and WHZ) in Lakshminiya Rural Municipality, Nepal. Materials and Methods: A community-based cross-sectional study was conducted from March to June 2021. The study included 308 children aged 6 to 59 months, selected using multistage random sampling. Data were collected through face-to-face interviews with mothers or primary caregiver and anthropometric measurements. Household sanitation indicators, such as improved sanitation, toilet conditions, waste disposal, and drinking water storage, were assessed. Data analysis was performed using SPSS 25, employing bivariate and multiple regression analyses to examine associations between household practices and nutritional outcomes. Results: The study found that improved household sanitation was positively associated with HAZ and WAZ. Improved toilet presence was also significantly correlated with WAZ and HAZ, while the association with WHZ was not significant. Cleanliness around toilets showed no significant associations with any of the nutritional indicators. Waste disposal practices, such as composting or burning, had an inverse relationship with WAZ. Covered drinking water storage was positively associated with WAZ but had no significant effect on HAZ or WHZ. Conclusions: Improved sanitation and covered drinking water storage are positively associated with better nutritional outcomes, particularly in HAZ and WAZ. These findings suggest the need for policies that promote improved sanitation and water storage practices to enhance child nutrition in rural Nepal.